Diet quality and depressive symptoms in adolescence: no cross-sectional or prospective associations following adjustment for covariates. Issue 13 (16th May 2018) - Winpenny, Eleanor M; van Harmelen, Anne-Laura; White, Martin; van Sluijs, Esther MF; Goodyer, Ian M
Abstract: Objective: Adolescence is a critical period for development of depression and understanding of behavioural risk factors is needed to support appropriate preventive strategies. We examined associations between adolescent diet quality and depressive symptoms, cross-sectionally and prospectively, in a large community cohort, adjusting for behavioural and psychosocial covariates. Design: Prospective community-based cohort study (ROOTS). Setting: Secondary schools in Cambridgeshire and Suffolk, UK. Subjects: Study participants ( n 603) who completed 4 d diet diaries at age 14 years and reported depressive symptoms (Moods and Feelings Questionnaire (MFQ)) at 14 and 17 years of age. Results: Diet data were processed to derive a Mediterranean diet score (MDS) and daily servings of fruit and vegetables, and fish. At age 14 years, a negative association between fruit and vegetable intake and MFQ score was seen in the unadjusted cross-sectional regression model ( β =−0·40; 95 % CI −0·71, −0·10), but adjustment for behavioural covariates, including smoking and alcohol consumption, attenuated this association. Fish intake and MDS were not cross-sectionally associated with MFQ score. No prospective associations were found between MDS, fruit and vegetable intake or fish intake and later MFQ score. Conclusions: Diet quality was not associated with depressive symptoms in mid-adolescence. Previously reported associations in this age range may be due to confounding. Further longitudinal studies are needed that investigate associations between adolescent diet and depression across different time frames and populations, ensuring appropriate adjustment for covariates.